2010
DOI: 10.5897/ajb09.967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant potential of medicinal plants from Malaysian Rubiaceae (subfamily Rubioideae)

Abstract: This paper evaluates the antioxidant potential of 22 species of medicinal plants from Malaysian Rubiaceae. The ferric thiocyanate (FTC), thiobarbituric acid (TBA), total phenolic content (TPC) and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays were employed. The tested extracts showed strong antioxidant potential when compared to butylated hydroxytoluene (BHT), quercetin and vitamin E with percent inhibition of 91-99% in the FTC, and 77-97% in the TBA assays. The TPC of extracts found varied from 8.55 to 120.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The total phenolic content of the M. pendens tubers using the ethanol solvent was 330.61 ± 2.13 mg GAE/g. In addition, Ahmad et al (2010) reported that the total phenolic content in 22 kinds of medicinal herbs from the Malaysian Rubiaceae family (subfamily Rubioideae) showed that Hydnophytum formicarum which had a close relative of Myrmecodia (but a different genus) possessed the highest total of phenolic contents compared to other plants (120.63 ± 3.09 mg GAE/g). …”
Section: Total Of Phenolic Content (Tpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The total phenolic content of the M. pendens tubers using the ethanol solvent was 330.61 ± 2.13 mg GAE/g. In addition, Ahmad et al (2010) reported that the total phenolic content in 22 kinds of medicinal herbs from the Malaysian Rubiaceae family (subfamily Rubioideae) showed that Hydnophytum formicarum which had a close relative of Myrmecodia (but a different genus) possessed the highest total of phenolic contents compared to other plants (120.63 ± 3.09 mg GAE/g). …”
Section: Total Of Phenolic Content (Tpc)mentioning
confidence: 99%
“…In a study conducted by Soeksmanto et al (2010), it was reported that the extract of ant-plants (M. pendens) could inhibit the growth of cervical and breast cancer cells (HeLa and MCM-B2 cells). Ahmad (2010) also stated that a total of high phenolic contents and antioxidant activity (AOA) of Hydnophytum formicarum could be used as an anti-oxidant and anti-microbial agent (Prachayasittikul et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Myrmecophytes used as medicine belong to Hydnophytum and Myrmecodia genera. Phytochemical analysis showed that Myrmecophyte tubers contain of flavonoids and tannins which have the properties of antiproliferative (Senawong et al, 2013), anticancer (Abdullah et al, 2010), antimicrobe (Ahmad et al, 2010), antioxidant (Dirgantara et al, 2013), antiinflammation, antiparasite, antimalarial, and antifungal (Musman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Rubiaceae family (Madder family) is one of the largest of the angiosperms with more than 637 genera and almost 10,700 species [1] . The genus Nauclea which belongs to this family, consists of about 35 species worldwide [2] and in Malaysia, there are two Nauclea species; N. officinalis and N. subdita [3] .…”
Section: Introductionmentioning
confidence: 99%